2012
DOI: 10.1080/13811118.2012.667321
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Preventing Military Suicide

Abstract: The continual rise in the U.S. military's suicide rate since 2004 is one of the most vexing issues currently facing military leaders, mental health professionals, and suicide experts. Despite considerable efforts to address this problem, however, suicide rates have not decreased. The authors consider possible reasons for this frustrating reality, and question common assumptions and approaches to military suicide prevention. They further argue that suicide prevention efforts that more explicitly embrace the mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 65 publications
1
68
0
2
Order By: Relevance
“…Military cultural norms may therefore pose a relatively greater vulnerability for male service members who have experienced military sexual trauma. Specifically, military cultural norms emphasize traditional masculine values such as physical and mental strength, toughness, and self-reliance (Brooks, 1990;Barrett, 1996;Jakupcak, 2003;Jakupcak et al, 2006;Levant and Richmond, 2007;Bryan et al, 2013a). Previous research has confirmed that cultural masculinity norms may impact mental health symptoms and interfere with treatment and recovery (Eisler et al, 1988;Carpenter and Addis, 2000;McDermott et al, 2010).…”
Section: Ideationmentioning
confidence: 93%
See 1 more Smart Citation
“…Military cultural norms may therefore pose a relatively greater vulnerability for male service members who have experienced military sexual trauma. Specifically, military cultural norms emphasize traditional masculine values such as physical and mental strength, toughness, and self-reliance (Brooks, 1990;Barrett, 1996;Jakupcak, 2003;Jakupcak et al, 2006;Levant and Richmond, 2007;Bryan et al, 2013a). Previous research has confirmed that cultural masculinity norms may impact mental health symptoms and interfere with treatment and recovery (Eisler et al, 1988;Carpenter and Addis, 2000;McDermott et al, 2010).…”
Section: Ideationmentioning
confidence: 93%
“…First, because of the collectivist orientation of the military and high salience of in-group identification (Bryan et al, 2013a), a service member who has been offended or victimized by another service member may experience a greater sense of betrayal and feel less willing to seek out assistance. Along these same lines, survivors of military sexual trauma may experience greater social isolation from others and a greater degree of emotional distress afterwards.…”
Section: Introductionmentioning
confidence: 99%
“…It is also the eleventh leading cause of death for all Americans and the third leading cause of death for American youth (Goldsmith et al, 2002). It is projected that suicide rates will rise into the foreseeable future (Mathers and Loncar, 2006) with some of this increase stemming from the dramatic rise in suicidality among United States veterans returning from foreign wars (Bryan et al, 2012). Reduction in suicide related injury and mortality is a stated goal of both the World Health Organization (World Health Organization, 1996) and the United States government (Satcher, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The repeated and seemingly endless episodes or gun violence that have horrified and terrified the nation are generating new advocates for better mental health programs. The large number of veterans returning home from Iraq and Afghanistan with posttraumatic stress disorder (PTSD), depression, and substance abuse and the increasing numbers and rates of suicides among veterans and the active military are eliciting public compassion [5]. The World Health Organization has publicized the large role that mental illness plays in the Global Burden of Disease [6], and policy makers and the public are beginning to recognize the huge impact mental illness has on driving up health care costs-including both costs resulting from mental illness itself and costs resulting from psychiatric comorbidities with non-psychiatric conditions [7,8].…”
Section: The Current State Of Mental Health Reformmentioning
confidence: 99%